PENGARUH TRANSAKSI NON TUNAI, INFLASI DAN PENERIMAAN PAJAK TERHADAP PERUMBUHAN EKONOMI DI INDONESIA - Merin Tri Lestari (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2021)
Economic growth is a development goal that every country wants to achieve, one of which is Indonesia, which is currently focus on increasing economic growth. Therefore, this study aims to analyze the effect of ATM and debit cards, electronic money, inflation and tax revenue on economic growth in Indonesia, either partially or simultaneously. This type of research uses a quantitative approach with multiple linear regression methods, data used are secondary data taken from the publications of the Central Statistics Agency, Bank Indonesia and the Ministry of Finance of the Republic of Indonesia in 2012-2018. The data in the study were processed using SPSS 26. Results of hypothesis testing showed that ATM and debit cards had a positive effect on economic growth, electronic money had a positive effect on economic growth. While inflation has no effect on economic growth and tax revenue has no effect on economic growth. Simultaneously, ATM and debit cards, electronic money, inflation and tax revenues have an effect on economic growth.